Prevalence and predictors of self-medication among university students in Ethiopia: a systematic review and meta-analysis - Getahun Fetensa; Tadesse Tolossa; Werku Etafa; Ginenus Fekadu (Taylor & Francis Group, 2021)
Background Self-medication of medicines is a global issue particularly among those with good access and familiarity with medications such as university students. It has a significant impact on drug resistance and medication-related complications. There are limited and inconsistent studies on self-medication practices in Ethiopia. The aim of this systematic review and meta-analysis was to estimate the pooled prevalence of self-medication and its predictors among university students in Ethiopia. Methods A systematic review and meta-analysis was conducted to assess the prevalence and predictors of self-medication among university students in Ethiopia. Published articles from various electronic databases such as Medline, Hinari, Pub Med, Cochrane library, and the Web of Science were accessed. In addition, a manual search was performed including Google Scholar. Searching of articles were searched from January 1st to February 1, 2021. All observational studies conducted among university students in English language were included in the review. Two reviewers independently assessed articles before inclusion in the final review using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) instrument for critical appraisal. The I 2 test was used to assess heterogeneity. Since the included studies exhibited high heterogeneity, a random-effects model was used to estimate the pooled prevalence of self-medication. Results We found of 812 published and unpublished studies in our search. Finally, 31 full-text studies were reviewed, and 13 studies fulfilled the inclusion criteria and were included in the final meta-analysis. A total of 5377 study respondents from 13 studies were included in the study. The results of our study revealed that the pooled prevalence of self-medication among university students was 49.41% (95% CI 38.67%, 60.13%). The included studies had a sample size ranging from 250 to 792 with the lowest prevalence (19.87%) of self-medication from the University of Gondar, whereas the highest prevalence (77.01%) was recorded in a study conducted at Arsi University. From the pooled estimation, there was a significant association between self-medication and income (OR = 0.67: 95% CI 0.55-0.80). However, the association between self-medication and year of study and sex of participants was insignificant. Conclusion The pooled prevalence of self-medication among Ethiopian university students was relatively high compared to the current global health problem with an increase in anti-microbial resistance. Health professionals and concerned bodies should pay attention to raising awareness regarding the consequences of using medications without prescription.